Prospek Hubungan Maritim Indonesia – Malaysia Pasca Kesepakatan Batas Laut 2023 - Muhammad Yuan Fauzil; Agussalim Burhanuddin (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This article discusses the Indonesia-Malaysia maritime boundary agreement reached in 2023. This paper uses a literature review method to analyze the historical and political context that guided the maritime boundary negotiations between the two countries, particularly highlighting the role of diplomacy and foreign policy in reaching the agreement. Furthermore, it explores the legal aspects of the maritime boundary agreement and its impact on territorial claims, sovereignty and natural resource exploration rights. In the context of international relations, the article discusses how the boundary agreement may affect regional dynamics in Southeast Asia, focusing on the roles of Indonesia and Malaysia as key actors in maritime security and economic development in the region. Comparisons with similar issues in the Asia Pacific region provide a broader perspective on the global implications of this agreement. In addition, this article explores the potential for bilateral collaboration in the areas of security, fisheries surveillance and marine disaster management. Sustainable utilization of natural resources and economic development through maritime cooperation are an important focus, with an emphasis on establishing equitable and sustainable exclusive economic zones. By analyzing all these aspects, this article aims to provide a deep insight into the prospects of maritime relations between Indonesia and Malaysia post the 2023 maritime boundary agreement, as well as provide policy recommendations to strengthen the two countries' cooperation in the maritime field.